L’ambivalence des communs - Gilles Allaire (Développement Durable et Territoires)
In many areas, resources are used and managed in common. The value of a common-pool resources, which today justifies the attention that is given to its management, reflects the anticipation of the achievements of an upcoming process of the resources units it provides. We qualify as intangible this dimension, shared by material, and more widely, types of common-pool resources, and we relate it to the concept of intangible property introduced by J. R. Commons. The Ostrom’s concept of commons has several facets. It is not only a system of resources (« common-pool resources »), but also a property regime and more widely a type of complex institutional arrangement, as well as the justifications given for it. We conceptualize the ambivalence of this concept by considering the institutional complexity and the temporal dimension of systems of collective resources.